Developmental regulation of hippocampal long-term depression by cofilin-mediated actin reorganization. (January 2017) - Cao, Feng; Zhou, Zikai; Pan, Xingxiu; Leung, Celeste; Xie, Wei; Collingridge, Graham; Jia, Zhengping
Abstract: Long lasting synaptic plasticity involves both functional and morphological changes, but how these processes are molecularly linked to achieve coordinated plasticity remains poorly understood. Cofilin is a common target of multiple signaling pathways at the synapse and is required for both functional and spine plasticity, but how it is regulated is unclear. In this study, we investigate whether the involvement of cofilin in plasticity is developmentally regulated by examining the role of cofilin in hippocampal long-term depression (LTD) in both young (2 weeks) and mature (2 months) mice. We show that both total protein level of cofilin and its activation undergo significant changes as the brain matures, so that although the amount of cofilin decreases significantly in mature mice, its regulation by protein phosphorylation becomes increasingly important. Consistent with these biochemical data, we show that cofilin-mediated actin reorganization is essential for LTD in mature, but not in young mice. In contrast to cofilin, the GluA2 interactions with NSF and PICK1 appear to be required in both young and mature mice, indicating that AMPAR internalization is a common key mechanism for LTD expression regardless of the developmental stages. These results establish the temporal specificity of cofilin in LTD regulation and suggest that cofilin-mediated actin reorganization may serve as a key mechanism underlying developmental regulation of synaptic and spine plasticity. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: The protein level and activity of cofilin are developmentally regulated. Hippocampal LTD requires cofilin in mature but not in young mice. Hippocampal LTD requires GluA2 interactions with NSF and PICK1 in both young and mature mice.